TikTok Application as English Learning Media - Eliza, Irma; Amanda, Rifka (English LAnguage Study and TEaching, 2023)
TikTok is a social media platform that allows users to create short videos accompanied by a variety of feature options such as music, filter stickers, and several other creative features. TikTok's popularity allows many users, especially young people, to take advantage of this platform to obtain information and knowledge through TikTok content. This research aims to examine whether TikTok can be an alternative and interactive learning media in English learning. This research used a qualitative method with an inductive approach. Research findings show that TikTok can make English learning interesting. It was found that there are several types of learning resources from the TikTok application that are often created, namely vocabulary, grammar, pronunciation and common mistakes. From this research, TikTok has an appeal as an English language learning medium, because short videos, clear and non-monotonous delivery of material, coupled with attractive writing effects and emoji features can have a positive impact on the students learning process.